Litwa w sarmackiej myśli historycznej doby oświecenia = Lithuania in the Sarmatian historical concepts of the Enlightment - Sierżęga, Paweł (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The reform camp associated with Stanisław August Poniatowski was aware that the introduction of reforms depends on the support of the gentry. The past was to function as the key to changes in the mentality, teach responsibility for national matters and show the directions of the transformations of the system. In this context the Polish - Lithuanian issue gained particular significance. The aim was to change the conservative perspective expressed by the conviction that the traditional social and political system of the way Poland was ruled, is perfect.
Keywords: historiografia; sarmatyzm; oświecenie; stosunki polsko-litewskie; Polska; Litwa